Effect of mercuric chloride on electrical parameters and anion fluxes in the toad skin - Castillo, Graciela (2005)
The amphibian skin, widely used for studying the transepithelial passage of electrolytes, exhibits anion pathways relatively specific for Cl-. We studied the effect of HgCl2, 1.0×10-4 M on its electrical parameters and unidirectional anion fluxes. In the presence of Cl-, the transepithelial conductance (G) of the isolated skin of the Bufo arenarum toad increased considerably following exposure to HgCl 2, whereas short-circuit current (SCC)-reflecting transepithelial Na+ transport-underwent only slight stimulation. Following the blockade of Na+ intake by amiloride, 1.0×10-4 M, the removal of Cl- from the solution bathing the epidermal border of the skin brought about a decrease in G, and gave rise to a gradient-induced SCC (SCCg) consistent with transepithelial passage of Cl- along its gradient. Addition of mercaptoethanol, 5.0×10-3 M to the bath containing Hg2+ fully reversed these effects. The increase in G was accompanied by an increase in the unidirectional (epidermal to dermal) fluxes of 36Cl- and 131I-, and a decrease in the passage of 99mTcO4-. These results show the effects of HgCl2 to be similar to those of theophylline, although exhibiting a different selectivity. Our data suggest that anion passage following exposure to HgCl2 is, like that stimulated by theophylline, predominantly if not exclusively transcellular, and does not involve a significant opening of the tight junctions.